Mobile Based E-Commerce Application with Whatsapp Notification for Transactions - Tuasikal, Afrizal Halim Naindhy; Ujianto, Erik Iman Heri (Program Studi Teknik Informatika Universitas Pamulang, 2026)
Online shopping has become an essential part of modern society. Various e-commerce platforms have emerged offering a wide range of products, yet most still focus primarily on selling new items. In fact, there is a growing need for a platform that can accommodate both new and used goods transactions within a single, user-friendly application. Moreover, many existing platforms lack direct integration with instant messaging services such as WhatsApp, resulting in delayed transaction information and potentially leading to miscommunication. To address these challenges, a mobile-based e-commerce application was developed using Flutter as the frontend framework, Flask as the backend API, and MySQL as the database. The main advantage of this application lies in its automatic WhatsApp integration, which enables real-time transaction notifications. Testing results show that the application functions properly and remains stable. The main features include registration, login, product addition, and product listing, along with additional features such as favorites marking, live streaming, and automatic WhatsApp notifications. This application is expected to serve as an effective solution to overcome current platform limitations and to support efficient and convenient buying and selling of both new and used goods.